Multimorbidity and its socio-economic associations in community-dwelling older adults in rural Tanzania; a cross-sectional study - Emma Grace Lewis; William K. Gray; Richard Walker; Sarah Urasa; Miles Witham; Catherine Dotchin (My University, 2022)
Objectives: This paper aims to describe the prevalence and socio-economic associations with multimorbidity, by both self-report and clinical assessment/screening methods in community-dwelling older people living in rural Tanzania. Methods: A randomised frailty-weighted sample of non-institutionalised adults aged≥60 years underwent comprehensive geriatric assessment and in-depth assessment. The comprehensive geriatric assessment consisted of a history and focused clinical examination. The in-depth assessment included standardised questionnaires, screening tools and blood pressure measurement. The prevalence of multimorbidity was calculated for self-report and non-self-reported methods (clinician diagnosis, screening tools and direct measurement). Multimorbidity was defned as having two or more conditions. The socio-demographic associations with multimorbidity were investigated by multiple logistic regression. Results: A sample of 235 adults participated in the study, selected from a screened sample of 1207. The median age was 74 years (range 60 to 110 inter-quartile range (IQR) 19) and 136 (57.8%) were women. Adjusting for frailty-weighting, the prevalence of self-reported multimorbidity was 26.1% (95% CI 16.7–35.4), and by clinical assessment/screening was 67.3% (95% CI 57.0–77.5). Adjusting for age, sex, education and frailty status, multimorbidity by self-report increased the odds of being fnancially dependent on others threefold (OR 3.3 [95% CI 1.4–7.8]), and of a household member reducing their paid employment nearly fourfold (OR 3.8. [95% CI 1.5–9.2]). Conclusions: Multimorbidity is prevalent in this rural lower-income African setting and is associated with evidence of household fnancial strain. Multimorbidity prevalence is higher when not reliant on self-reported methods, revealing that many conditions are underdiagnosed and undertreated.
Keywords: Multimorbidity, Older people, Sub-Saharan Africa, Frailty